2017
DOI: 10.24263/2225-2924-2017-23-4-31
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pâté Using the Сноісе Phytocomplex of Cereal Cultures

Abstract: Key words: ABSTRACT Pâté Health and preventive nutrition The СНОІСЕ phytocomplex of germinated cereal cultures Quality indicesThe article presents the results of the research on the developed pâté using the СНОІСЕ phytocomplex of cereal crops (germinated oats, barley, wheat and corn). According to the organoleptic, physicochemical and functional-technological indicators, it has been established that the optimum content of phytocomplex of cereal crops in the pâté formulation is 15%. The results of the study con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The study of the chemical composition of the developed pates showed that the nutritional value of new formulations meet the requirements that are put forward to this assortment group. Physicochemical indices showed that the developed pastes have a low mass fraction of fat, high protein content, which leads to a decrease in energy value [3,4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of the chemical composition of the developed pates showed that the nutritional value of new formulations meet the requirements that are put forward to this assortment group. Physicochemical indices showed that the developed pastes have a low mass fraction of fat, high protein content, which leads to a decrease in energy value [3,4].…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the amino acids has shown that the prototype contains all the essential amino acids necessary. In polycomponent systems of developed pastes limiting amino acid is valine + isoleucine, which is typical of forcemeat with plant material [2,4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation